Pengaruh Model Pembelajaran Koopeatif Learning Tipe TGT Terhadap Hasil Belajar Siswa Bidang Studi PAI di SMPN 01 Sungai Pua - Febrizul Azmi; Wedra Aprison; Iswantir M; Junaidi Junaidi (Universitas 45 Surabaya, 2023)
The low learning outcomes of students are the background to the problem in this research. Based on data on study results for the odd mid-semester exam for class VII students at SMPN 01 Sungai Pua for the 2022/2023 academic year, 62% of students had scores below the passing criteria. Because of this, updates were made to convey material to students, researchers implemented the TGT cooperative learning model to students in the learning process. The aim of this research is to determine the difference between the application of the Teams Games Tournaments (TGT) learning model and conventional learning on PAI learning outcomes for class VII students at SMPN 01 Sugai Pua on the subject of Andalusia: The City of Islamic Civilization. From hypothesis testing using SPSS software, the significance score (2-tailed) = 0.010 < α = 0.05 and the significance score (2-tailed) < α so that H0 is rejected. It can be concluded that